Complex Oscillation of Differential Polynomials Generated by Meromorphic Solutions of $[p,q]$ Order to Complex Non-Homogeneous Linear Differential Equations (Journal of Mathematical Study, 2017)
In this article we study the complex oscillation of differential polynomialsgenerated by meromorphic solutions of the non-homogeneous linear differential equation $$f^{(k)}+A_{k-1}(z)f^{(k-1)}+...+A_1(z)f'+A_0(z)f=F,$$ where $A_i(z)(i=0,1, ...,k-1)$ and $F$ are meromorphic functions of finite $[p,q]$-order inthe complex plane.
Keywords: Non-homogeneous linear differential equations; differential polynomials; meromorphic solutions; $[p; q]$-order.